Agribusiness Model Based on Creating Shared Value in Optimizing Nonproductive Land in Plantation Areas - Kharisma Arta; A. C. Tridakusumah; Iwan Setiawan (Green Publisher Indonesia, 2026)
This research examines the economic and social impacts of the Plantation Community Empowerment Program (PMDK) and develops a Creating Shared Value (CSV)-based agribusiness model through the optimization of non-productive land in plantation areas. Although the application of CSV in agribusiness has increased, studies that explain the integrated mechanisms linking land optimization, community empowerment, and agribusiness systems remain limited. This research employed a qualitative case study approach at PTPN I Regional 2, Indonesia, involving 16 key informants from company management, field officers, local communities, and village government representatives. Data were collected through in-depth interviews, field observations, and documentation involving key stakeholders and analyzed using triangulation techniques. The findings reveal that the PMDK program increased land utilization by 60–70% and community income by 60–150%, with some cases reaching up to threefold growth. The program also improved access to agribusiness activities, reduced land conflicts, and strengthened social relations. However, constraints persist in capital access, human resource capacity, and market integration. This study proposes an integrative CSV-based agribusiness empowerment model that positions non-productive land as a strategic entry point for generating shared economic and social value. The findings contribute by offering a more comprehensive framework that links resource optimization, stakeholder collaboration, and agribusiness system integration in plantation-based rural development